Lean office aplicado à otimização do processo de aquisição de materiais de consumo: o caso do Instituto UFPB de Desenvolvimento da Paraíba - Lima, Osiran Felício de (2019)
Internal Institutional Evaluation has assumed the role of diagnosing the institution, recording the current situation and, based on the system's criteria and extensive discussion, identifying opportunities for improvement that result in better standards of efficiency and quality of its internal processes, both academic and institutional. administrative In this context, this research aims to analyze and propose improvements to the process of acquisition of consumables in a Federal Higher Education Institution (IFES), in this case the Federal University of Paraíba (UFPB), from the application of concepts and practices. Lean Office, with a focus on eliminating key process losses, with a view to increasing the potential for adding value to the activities undertaken and thus resulting in faster response to demands. Given the context of the research, a bibliographic survey involving Public Administration, New Public Management (NPM), Institutional Evaluation, Procurement in the public sector, and then on the concepts of Lean Production, which was unfolded in the content that deals with Lean Office, also known as Lean Office. It was adopted as a research modality the case study applied to the process of acquisition of consumables within the UFPB Institute of Development of Paraíba (IDEP-UFPB), supplementary body linked to the Rectory / UFPB. In data collection, in addition to the use of specific techniques (SIPOC, Flowchart and VSM) with the objective of mapping the value stream covering all stages that make up the process of acquisition of consumables, since the request in the Registration System of Prices (SRP) Until receipt of the items by the requesting sector, the documentary research and semi-structured interview with the servers involved were used. In the end, a theoretical contribution was obtained in the foreground, since the concepts and practices of the Lean Office model were applied in a public sector administrative environment, which presents very marked differences in relation to that environment where Lean practices are generally Secondly, the construction of future scenarios based on the principles of lean mentality pointed to the possibility of increasing the percentage of value added in relation to the Activity Cycle Time (TAV) from 54.8% to 63%. , 3%, and the potential value-added regarding the number of procedures (VAt), from 46.9% to 55.6%. Due to the projected improvements, Total Cycle Time (TCT) could be reduced by up to 26.3%, and Total Lead Time (TLT) decreased by 57.9% (Scenario I) and 75.9% (Scenario II). Thus, it was concluded that it is possible to optimize the consumables procurement process, from requisition to receipt, from a value stream design based on Lean Office theories, resulting in greater process efficiency and, therefore faster delivery of services within the public sector.